Vascular Surgery : A Global Perspective - Dardik, Alan (Springer International Publishing : Imprint: Springer, 2017)
Vascular Surgery: A Global Perspective provides the first review and comparison of the diversity of vascular surgery practice around the world. The book is grouped according to common vascular diseases such as aneurysmal and occlusive arterial disease, as well as venous and lymphatic disease and dialysis access. Each major disease topic includes multiple chapters written by expert specialists from around the world, each discussing their local approach to the disease and its treatment. Similarly, the status of vascular surgery practice is addressed, including discussion of the influence of payment systems on practice, patient access to the internet for information, training paradigms, and the legal system including malpractice. This textbook provides the first worldwide summary of the care of patients with vascular disease and will be of interest to a wide audience including vascular surgeons, vascular medical specialists, cardiologists, radiologists, internists, and family practice physicians.
Keywords: Medicine.; Forensic medicine.; Interventional radiology.; Cardiology.; Vascular surgery.; elektronické knihy; electronic books